الأسطوانة الإرتجالية وفعاليتها في تعليم مهارة القراءة بمدرسة هداية المبتدئين الثانوية الاسلامية مالانق - Samsul Maarif (Abjadia, 2016)
يهدف هذا البحث إلى (1) معرفة عملية صناعة المواد التعليمية الحاسوبية على شكل الأسطوانة، و(2) معرفة مدى فعالية استخدام الأسطوانة الإرتجالية لتعليم مهارة القراءة  في مدرسة هداية المبتدئين الثانوية الاسلامية مالانج. وأما نتائج البحث فهي (1) صناعة المواد التعليمية و الأسطوانة الإرتجالية، (2) معيار نتيجة اختبار الطلبة قبل استخدام الأسطوانة الإرتجالية 55،88% وبعد استخدامها 90،64%، وهذا يدل على ارتقاء 35،76%، (3) استبانة الطلبة حصلت على 76،35% ومعناها جيّدة وفعّالة. وتوصيات هذا البحث هي (1) إن في هذه الأسطوانة الإرتجالية خمس تدريبات في قياس مهارة القراءة لدى الطلبة، رجاء إلى الباحثين الآخرين أن يزيدوا التدريبات الموجودة، (2) الباحثين الأكادميكيين أن يدرّسوا اللغة العربية بطريقة أو بوسائل التعليم المتنوعة مملوءة بالفرح، (3) تختص هذه الأسطوانة الإرتجالية لتعليم مهارة القراءة للفصل الثاني عشر  المدرسة الثانوية الإسلامية، رجاء لللباحثين الآخرين أن يصمموا المواد التعليمية الآخر لمهارة الإستماع والكلام والكتابة.The purpose of this study there were two, namely 1) production hand-book and interactive CD to increase the reading skill (Research Development at Islamic Senior High School of Batu, 2) test the effectiveness of hand-book in increasing reading skill in the students Islamic Senior High School of Batu. Result of this research are 1) product hand-book arabic reading and interactive CD, it ist based on theories of teaching and curriculum arabic teaching of Islamic Senior High School. 2) the result of validation testing performed on experts suggest that interaktif CD is organized in categories including best and can be used directly in the learning without revision, while the small group testing shows that the interactive CD is included in both categories and can be used directly in the learning with a little revision. Student test results before using interactive CD shows the value 54,88% that indicates that the value of reading skills of students for reading is Low undersirable). As for the use interactive CD, found of a significant increase in the total value is 90,64%, this indicates that their value has increased accepted). While reseachers suggestions presented are 1) should be the intensification of efforts to teach reading material other Arabic as a manifestation of the development of teacher quality in particular Arabic and arabic Language teaching in Indonesia general, 2) for researchers interested in doing further similar research, is expected to produce a interactive CD that provides exercices based on the for laguage skills.